1993
DOI: 10.1038/hdy.1993.59
|View full text |Cite
|
Sign up to set email alerts
|

Sex determination in the hymenopteran Diadromus pulchellus (Ichneumonidae): validation of the one-locus multi-allele model

Abstract: Males of the hymenopteran Diadromus puichellus are normally haploid, but diploid males can be obtained by inbreeding. Inbred crosses within strains that are polymorphic at the enzymatic loci Pgm-2 and Ao-4 or that differ by a body colour mutation produce heterozygous diploid males in offspring. The genotypic distributions observed in such progeny were compared with expected results under the one-locus sex determination model or the two independent loci model. The results show that only the one-locus multi-alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 21 publications
1
39
1
Order By: Relevance
“…(1985) detected heterozygous males of this ichneumonoid wasp in an allozyme study and demonstrated cytologically that they were diploid. Subsequently, Periquet et al (1993) conducted breeding experiments in which diploid males were distinguishable as either allozyme or body colour heterozygotes and the data were consistent with single-locus but not two-locus CSD.…”
Section: Jmcookmentioning
confidence: 89%
See 1 more Smart Citation
“…(1985) detected heterozygous males of this ichneumonoid wasp in an allozyme study and demonstrated cytologically that they were diploid. Subsequently, Periquet et al (1993) conducted breeding experiments in which diploid males were distinguishable as either allozyme or body colour heterozygotes and the data were consistent with single-locus but not two-locus CSD.…”
Section: Jmcookmentioning
confidence: 89%
“…Periquet et al (1993) suggested that multilocus CSD might evolve from single-locus CSD by tandem duplication of the sex locus, followed by dispersal of the repeated genes to other chromosomes. If different allelic products lead to femaleness, the subsequent evolution of a multiple locus system would require that the female-producing reaction is somehow restricted within loci (Bull, 1981).…”
Section: Jmcookmentioning
confidence: 99%
“…Several studies suggested their results might be better explained by ml-CSD rather than sl-CSD (Garofolo 1973;Kerr 1974;Naito et al 2000), while others found no support for ml-CSD in a range of other species (Skinner and Werren 1980;Cook 1993a;Periquet et al 1993;Butcher et al 2000;Niyibigira et al 2004a;Schrempf et al 2006). Here, we show that inbreeding the braconid wasp C. vestalis for eight generations results in increasing proportions of DM and an increasingly male-biased sex ratio (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Diploid males are effectively sterile as they produce diploid sperm (MacBride, 1946). This system of single locus complementary sex determination (CSD) has also been demonstrated in another parasitoid wasp Diadromus puichellus (Periquet et a!., 1993), as well as the bees Apis mellifera (Mackensen, 1951;Woyke, 1965) and A. cerana (Woyke, 1979;Hoshiba eta!., 1981) and the sawfly Athalia rosae (Naito & Suzuki, 1991). It appears that single locus CSD also operates in the sawfly Neodiprion nigroscutum (Smith & Wallace, 1971), the fire ant Solenopsis invicta (Hung et a!., 1972(Hung et a!., , 1974Hung & Vinson, 1976;Ross & Fletcher, 1985, 1986 and the stingless bee Melipona quadrifasciata (Camargo, 1979), although data from these species do not strictly exclude a multilocus model (Cook, 1993).…”
Section: Introductionmentioning
confidence: 99%